Hydrogeological model from hydrochemical and geocryologic records on the Cape Lamb of Vega Island, northern Antarctic Peninsula - Silva-Busso, A. (2013)
The rapid changes that are taking place in the climate of the Antarctic Peninsula are triggering hydrological processes which had been limited or inactive for relatively long periods of time. These processes are evident in ice-free areas on the northern edge of the Antarctic Peninsula, such as Cape Lamb, and lead to intense draining of the surface and groundwater system throughout the brief Antarctic summer. The result is a movement of large amounts of water, sediments and nutrients that would be immobilized in other scenarios. This study proposes a model of the operation of the surface and groundwater system that could be valid for several ice-free areas in the region, based on the interpretation of field observations in Cape Lamb, the most extensive ice-free area on Vega Island. The model proposed is further supported by the interpretation of 56 chemical analyses of samples representing groundwater, active layer water, glacier ice and snowfall. The hydrochemical interpretation is supported primarily by four indicators (pH, electrical conductivity, D/18O ratio and SO4/Cl ratio) which have proven to be the most appropriate hydrochemical variables to differentiate the origin and interaction of the waters in the various sections of the system.